Value Stream Mapping of Rope Manufacturing: A Case Study. (16th February 2017) - Yuvamitra, Korakot; Lee, Jim; Dong, Kanjicai
Abstract : In today's competitive market place, manufacturing companies must apply continuous process improvement in order to maintain a returning customer base. One way of achieving constant process improvement is through value stream mapping. Value stream mapping is used to visualize the current processes for easier understanding and problem identification. A well-defined problem statement will ensure a successful outcome of a project improvement process. This research provides a case study performed on a rope manufacturing process. A current state value stream map is created, and the possible improvements are suggested. The implemented results are shown in the form of future state map. The results show that, after waste elimination and structural revision, a manufacturing process becomes more efficient, enabling the customer to receive an order significantly faster.